Incorporating fish habitat requirements of the complete life cycle into ecological flow regime estimation of rivers. Issue 4 (11th March 2020) - Wang, Li; Chen, Qiuwen; Zhang, Jianyun; Xia, Jun; Mo, Kangle; Wang, Jun
Abstract: Maintenance of ecological flow regime for aquatic biota is essential to river ecosystem health. To estimate ecological flow, habitat simulation methods have been widely applied because of their combination of hydrological regime and species hydraulic preference. However, few methods are available to provide a flow regime that varies over time due to time‐specific habitat requirements from different target species or from one target species at its different life stages. This paper described a novel approach for evaluating the ecological flow regime that was a time series of discharge considering different life stages of target species. First, an ecohydraulic model that combined multivariable habitat suitability curve of target species with a hydraulic module was developed to establish the relationship between habitat status and hydrological conditions. Then, the habitat connectivity index was adopted to assess the spatial patterns of habitat patches. Finally, the ecological flow regime considering the complete life cycle of target species was derived. The developed approach was applied to the middle reach of Huaihe River, where the flow is highly regulated by dams and sluices. The Chinese bream ( Parabramis pekinensis ) was chosen as the target species for ecological flow calculation. The ecological flow regime in the Lutaizi was provided for the river management. The study provided a promising method to support ecological friendly operations of hydraulic structures for river ecosystem restoration and management.